ANALISIS DINAMIKA PENYALURAN KREDIT PT.PEGADAIAN WILAYAH VI SEMARANGTAHUN 2011 – 2012 (Students' Journal of Economic and Management, 2015)
The purpose of this study is to analyze the dynamics of credit non-bank financial institutions engaged in services Pegadaian. Analysis of the dynamics of the dynamic impact analysis from the aspects of influence Bi rate, Inflation, and Exchange . Object of research is PT. Pegadaian Region 6 Semarang data used are secondary data monthly period 2011-2012. Analysis of data using multiple regression analysis with the help of Eviews program. The conclusion of this study is : BI rate and the exchange rate does not significantly influence the amount of credits while inflation has a negative influence on the amount of credit. Keywords: BI Rate, Inflation, Exchange Rate and Amount of Credit